2009
DOI: 10.1002/jor.20906
|View full text |Cite
|
Sign up to set email alerts
|

VEGF serum concentrations in patients with long bone fractures: A comparison between impaired and normal fracture healing

Abstract: Vascular endothelial growth factor (VEGF) plays an important role in the bone repair process as a potent mediator of angiogenesis and it influences directly osteoblast differentiation. Inhibiting VEGF suppresses angiogenesis and callus mineralization in animals. However, no data exist so far on systemic expression of VEGF with regard to delayed or failed fracture healing in humans. One hundred fourteen patients with long bone fractures were included in the study. Serum samples were collected over a period of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 26 publications
5
47
2
Order By: Relevance
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
“…Patients gave informed written consent to be enrolled in the study, and were 18-90 years old. The recruitment parameters, sample collection schedule, matching process, patient demographics and exclusion criteria of this study have been previously published in detail [8][9][10]. In brief, between 2006 and 2008 a consecutive series of 113 patients with meta-/ diaphyseal fractures of long bone (humerus, femur, lower leg and forearm) and surgical treatment were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we analysed the expression of important osteogenic growth factors M-CSF, VEGF and TGF-ß1 during the fracture healing process with and without the use of LMWHs to detect a possible impact. Numerous studies have previously shown that the growth factors measured in our study play a cardinal role in the regulation of human fracture healing [4,[24][25][26]. Interestingly, our results could not confirm the results of the experimental studies as we did not observe a significant decrease in the expression of the analysed growth factors due to the use of enoxaparin.…”
Section: Discussioncontrasting
confidence: 94%
“…VEGF is known to be an important factor for angiogenesis and bone formation [22]. Moreover, VEGF is actively involved in the process of fracture healing [23,24]. Oncological studies have shown that LMWHs prolong survival time not only by having antithrombotic properties but also by their antiangiogenic effect [18][19][20].…”
Section: Discussionmentioning
confidence: 99%